Relationships Between Personal Values and Leadership Behaviors in Basketball Coaches - Castillo, Isabel; Adell, Francisco L.; Alvarez, Octavio (Frontiers in Psychology, 2018)
Background: Based on the refined theory of basic individual values and transformational leadership theory, this study focuses on the associations between coaches’ value priorities and their transformational leadership behaviors, exploring the potential mediation versus moderation effect of two alternative variables in this relationship: perceived club pressure or an autonomy supportive environment. Methods: Participants were 266 basketball coaches (85.7% men) from 17 to 66 years old (M = 32.82, SD = 9.2) from 119 different Spanish clubs. On average, they had worked for their current sport clubs for 5.02 years, and they had a mean of 11.10 years of experience. The coaches were all Spanish speakers, and they trained players at different levels of competition. Results: The stronger the importance of the coaches’ self-transcendent values (i.e., universalism and benevolence), the more they displayed transformational behaviors (i.e., individual consideration, inspirational motivation, intellectual stimulation, and fostering acceptance of group goals) toward the basketball players and perceived a more autonomy supportive environment and lower pressure from the club. Coaches who held conservation values (i.e., humility and face) displayed inspirational motivation behaviors. When coaches held openness to change values (i.e., stimulation and self-direction thought), they tended to display inspirational motivation and intellectual stimulation. Finally, coaches who held beliefs in self-enhancement values (i.e., power) displayed lower transformational behaviors (intellectual stimulation and fostering acceptance of group goals) toward their basketball players, and they perceived higher pressure from the club and a less autonomy supportive environment. Moreover, the club’s autonomy supportive environment played a mediator role between self-transcendence values and some transformational behaviors; however, moderator effects were not significant, with the exception of coaches with self-enhancement values, who tended to avoid intellectual stimulation to a larger extent when they perceived high levels of pressure at the club. Conclusion: These results highlight the importance of identifying the value base on which to develop transformational leadership programs in order to enhance positive experiences in the sport domain.